Factors associated with loneliness in Latin-American family care partners during the COVID-19 pandemic - Leon, Tomas; Tapia-Munoz, Thamara; Slachevsky, Andrea; Beber, Bárbara Costa; Aguzzoli, Fernando; Nubia, Carla; Vilar-Compte, Mireya; Gaitan-Rossi, Pablo; Olavarria, Loreto; Castro, Loreto; Pinto, Alejandra; Guajardo, Tania; et al. (Frontiers in Psychiatry, 2024)
Background: COVID-19-related restrictions led to an increase in overall loneliness and social isolation. Before the pandemic, care partners reported higher levels of loneliness and higher loneliness prevalence compared to non-care partners. Because of the spread and severity of the infections, and the access to support spread, we expect a different impact of the COVID-19 pandemic on LATAM care partners. Objectives: To describe the loneliness levels of LATAM caregivers and to identify socioeconomic and health factors associated. Design: An international online cross-sectional survey for care partners, embedded within the 'Coping with Loneliness and Isolation during COVID-19' (CLIC) Study conducted between June 2020– and November 2020. Setting: We analysed data from 246 family care partners living in Latin American countries (46% Mexico, 26% Chile,18% Brazil, and 10% from Argentina, Peru, Venezuela, Panama, Guatemala y Costa Rica) Measurements: We assessed loneliness using the 6-items of De Jong Gierveld loneliness Scale. We described the levels of overall, emotional, and social loneliness pre and during Covid, and reported the distribution of care partners who improved, worsened or maintained their levels of loneliness. Moreover, we used longitudinal multiple linear regression models with bootstraps errors of 1,000 iterations to identify factors associated with the levels of overall, emotional, and social loneliness during the pandemic. Results. Participants were mostly women, 50 years and older, in a partnership, highly educated and with finances meeting their needs, with good to excellent physical and mental health. Among the total of care partners, 55% perceived higher overall loneliness, 56% higher emotional loneliness, and 21% higher social loneliness during the pandemic in comparison with pre-COVID-19 levels. Perceived mental health was associated with the overall, emotional, and social loneliness. Conclusions. Regardless of their living and health situation, during the pandemic, loneliness increased in all groups of care partners. These should be taken in consideration when planning public health approaches for crises such as pandemics or other large-scale disruptive events.